Olfactory kin recognition in a songbird - Krause, E. Tobias (The Royal Society, 2012)
The ability to recognize close relatives in order to cooperate or to avoid inbreeding is widespread across all taxa. One accepted mechanism for kin recognition in birds is associative learning of visual or acoustic cues. However, how could individuals ever learn to recognize unfamiliar kin? Here, we provide the first evidence for a novel mechanism of kin recognition in birds. Zebra finch (Taeniopygia guttata) fledglings are able to distinguish between kin and non-kin based on olfactory cues alone. Since olfactory cues are likely to be genetically based, this finding establishes a neglected mechanism of kin recognition in birds, particularly in songbirds, with potentially far-reaching consequences for both kin selection and inbreeding avoidance.